Electrochemical Synthesis of Glycine from Oxalic Acid and Nitrate. (26th August 2021) - Kim, Jeong Eun; Jang, Jun Ho; Lee, Kyu Min; Balamurugan, Mani; Jo, Young In; Lee, Moo Young; Choi, Seungwoo; Im, Sang Won; Nam, Ki Tae
Abstract: In manufacturing C−N bond‐containing compounds, it is an important challenge to alternate the conventional methodologies that utilize reactive substrates, toxic reagents, and organic solvents. In this study, we developed an electrochemical method to synthesize a C−N bond‐containing molecule avoiding the use of cyanides and amines by harnessing nitrate (NO3 − ) as a nitrogen source in an aqueous electrolyte. In addition, we utilized oxalic acid as a carbon source, which can be obtained from electrochemical conversion of CO2. Thus, our approach can provide a route for the utilization of anthropogenic CO2 and nitrate wastes, which cause serious environmental problems including global warming and eutrophication. Interestingly, the coreduction of oxalic acid and nitrate generated reactive intermediates, which led to C−N bond formation followed by further reduction to an amino acid, namely, glycine. By carefully controlling this multireduction process with a fabricated Cu–Hg electrode, we demonstrated the efficient production of glycine with a faradaic efficiency (F.E.) of up to 43.1 % at −1.4 V vs. Ag/AgCl (current density≈90 mA cm −2 ). Abstract : By electrochemical method, stable oxalic acid and nitrate substrates were coupled into an amino acid, glycine. Insertion of electrons resulted in their conversion into nucleophile and electrophile, respectively, which led to C=N bond formation between them, as well as the conversion of the reversible C=N double bond to a stable C−N single bond.